Influence of ultimate muscle pH on the microbial quality of black wildebeest (Connochaetes gnou) meat - Makasi, Thandeka Nedia (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc Food Sc)--Stellenbosch University, 2015.